1977
DOI: 10.1115/1.3450675
|View full text |Cite
|
Sign up to set email alerts
|

Study of Frost Properties Correlating With Frost Formation Types

Abstract: Frost formation process was studied by photographic observation, and frost formation types were classified into several groups according to their structure in the temperature range of 0 ∼ −25°C. Frost properties, density and effective thermal conductivity, were clarified in connection with the classified frost formation types, and the prediction of the thermal conductivity was performed by the presented structural model of a frost layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
104
0
3

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 307 publications
(123 citation statements)
references
References 0 publications
4
104
0
3
Order By: Relevance
“…Rite and Crawford [8] studied experimentally the effects of various parameters on the rate of frost formation on the domestic refrigerator-freezer finned tube heat exchanger coil with 5.1 mm of fin space. Hayashi [9] found that the amount of frosting gets larger at the entrance of an air flow, in agreement with the general results of other papers. Schneider [10] simulated frost height by balancing the heat transfer rate between vapor diffusivity on frost surface and thermal conductivity between frost layers of a parallel plate heat exchanger.…”
Section: Introductionsupporting
confidence: 81%
“…Rite and Crawford [8] studied experimentally the effects of various parameters on the rate of frost formation on the domestic refrigerator-freezer finned tube heat exchanger coil with 5.1 mm of fin space. Hayashi [9] found that the amount of frosting gets larger at the entrance of an air flow, in agreement with the general results of other papers. Schneider [10] simulated frost height by balancing the heat transfer rate between vapor diffusivity on frost surface and thermal conductivity between frost layers of a parallel plate heat exchanger.…”
Section: Introductionsupporting
confidence: 81%
“…This model was validated over the full range of frost surface temperature. Note that the widely used correlation of Hayashi et al [24] expresses frost density dependent on frost surface temperature only, and is known to considerably overpredict the frost density at relatively high frost surface temperatures close to the melting temperature [14].…”
Section: Frost Densitymentioning
confidence: 99%
“…(e.g. Mao et al (1999), Hayashi (1977), Storey and Jacobi (1999), Ostin and Andersson (1991), Yonko and Sepsi (1967)). A comprehensive review of the effect of frosting on heat exchangers is provided by Kondepudi and O'Neal (1987) who also investigated the frost growth effects on the performance of heat exchangers with flat and louvered fins.…”
Section: Introductionmentioning
confidence: 99%